A diminutive Pliocene guenon from Kanapoi, West Turkana, Kenya. Issue 135 (October 2019) - Plavcan, J. Michael; Ward, Carol V.; Kay, Richard F.; Manthi, Fredrick K.
Abstract: Although modern guenons are diverse and abundant in Africa, the fossil record of this group is surprisingly sparse. In 2012 the West Turkana Paleo Project team recovered two associated molar teeth of a small primate from the Pliocene site of Kanapoi, West Turkana, Kenya. The teeth are bilophodont and the third molar lacks a hypoconulid, which is diagnostic for Cercopithecini. The teeth are the same size as those of extant Miopithecus, which is thought to be a dwarfed guenon, as well as a partial mandible preserving two worn teeth, previously recovered from Koobi Fora, Kenya, which was also tentatively identified as a guenon possibly allied with Miopithecus . Tooth size and proportions, as well as analysis of relative cusp size and shearing crest development clearly separate the fossil from all known guenons. Based on the Kanapoi material, we erect a new genus and species, Nanopithecus browni gen. et sp. nov. The small size of the specimen suggests either that dwarfing occurred early in the lineage, or at least twice independently, depending on the relationship of the new species with extant Miopithecus . Further, the distinctive habitat and geographic separation from Miopithecus suggests that the origin of small body size is not uniquely linked to the current habitat of Miopithecus, and possibly that relatives of extant Miopithecus were much more widely distributed in the past. This in turn argues caution in using extant biogeography in models of the origins of at least some guenons.